Effect of Auditor Choice and Tenure on the Cost of Equity Capital of Selected Listed Firms in the Philippines - Borja, Daniel Vincent H. (Philippine Management Review; Vol 22 (2015), 2015)
This study examines the empirical evidence of the effects of auditor choice, using audit firm size and audit firm switches as proxies, and auditor tenure, using audit firm tenure and engagement partner rotation as proxies, on the equity costs of capital of local companies listed in the Philippine Stock Exchange. Focusing on listed companies from the Property, Financial Institutions and Energy & Utilities sectors, a sample of 308 firm-year observations from the period 2004-2011 was included in the study. Using Pooled Ordinary Least Squares and including Company Growth Opportunities, Leverage and Company Size as control variables, various regression models were estimated to test the various hypotheses. A cross-sectional regression model was used to test the effect of audit firm tenure on the cost of equity capital using 2010 as base year. The results show that proxies for the size of the audit firm and tenure of the firm as auditor are statistically significant. The results of the study indicate that Auditor Competence is assessed and consequently measured by the stakeholders, stockholders in particular, in their valuation of information risk. Thus, the audit quality variables Audit Firm Size and Audit Firm Tenure, identified by this study as significant, act as signals to the stockholders or other stakeholders of the level of credibility of the financial statements that they depend on in making sound economic decisions.